METHODS AND TECHNIQUES OF WORKING ON SPEECH STYLES IN RUSSIAN LANGUAGE LESSONS AT UZBEK SCHOOL (Методы и приёмы работы над стилями речи на уроках русского языка в узбекской школе) - Yusupova Feruza Abdrasulievna (Journal of new century innovations, 2022)
Abstract: the article discusses methods and techniques of working on speech styles in Russian language lessons in an Uzbek school.